Integrating Financial Education and Digital Innovation to Enhance Financial Behavior in Heritage-Based Microenterprises in Malang City - Abidin, Zahroh; Pamungkas, Maria Goretti Wi Endang Nirowati; Utami, Rachma Bhakti; Yuniarto, Saiful Rahman; Nurtjahjono, Gunawan Eko (Economics, Business, Accounting & Society Review, 2025)
The rapid growth of digital technology and the increasing importance of financial literacy have redefined entrepreneurial behavior, particularly among small business owners in developing countries. In Indonesia, many small and medium enterprises (SMEs) continue to face challenges in financial management and technology adoption, especially in heritage-based economies such as Kampoeng Heritage Kajoetangan, Malang City. This study aims to examine the relationship between financial education, digital innovation, and financial behavior among micro and small entrepreneurs operating within this cultural and economic setting. This research employs an explanatory quantitative design using survey data collected from 50 SMEs. The data were analyzed through Partial Least Squares (PLS) to test the structural relationships between the variables. The results reveal that both financial education and digital innovation have positive and significant effects on financial behavior, with financial education demonstrating a stronger influence. Entrepreneurs with higher financial literacy tend to exhibit more responsible financial decision-making, while digital innovation enhances financial efficiency and accessibility through technology-based operations. These findings underscore the complementary role of education and digital innovation in fostering rational and sustainable financial behavior among SMEs. The study highlights the importance of integrating financial literacy programs with digital capacity-building initiatives to strengthen entrepreneurial resilience. Policymakers are encouraged to design targeted interventions that expand access to financial education and digital infrastructure, particularly in cultural tourism areas where micro enterprises play a key role in local economic development.